Bryophytic remains from the early Permian sediments of India - Chandra, Shaila (Journal of Palaeosciences, 1994)
Bryophytic fossil remains in the Permian Gondwana formations are extremely rare. The rarity of fossil bryophytes is generally attributed to their delicate nature and small size of the plants. Fossil bryophytes so far reported are few as compared to vascular plants but they have been adequately recorded to indicate early existence of mosses and liverworts. It is also likely that bryophytes have just not been recognized in ancient sediments by palaeobotanists and they may not be so rare as are believed today. Most of the fossil specimens reported from India as bryophytes are either doubtful records or unidentifiable up to generic level, Indian Permian reports are considered doubtful while Triassic and younger records are not so meagre and are reasonably well reported. It is for the first lime a good assemblage of bryophytes has been recovered from the Early Permian sediments of India as impressions along with the typical Glossopteris flora. Both the groups Hepaticae and Musci are represented by newly designated form genera and species. The assemblage is represented by an indeterminate genus - Bryothallites talchirensis, hepatic genus- Hepaticites umariaensis, and three moss genera- Talchirophyllites indicus, Saksenaphyllites saksenae and Umariaphyllites acutus. Remarks on the naming of the fossil bryophytes, their probable possibility of preservation, spore distribution, probable habitat and evolutionary aspects also have been given and discussed.